The Effect of Diaphragmatic Breathing as a Complementary Therapeutic Strategy in Stress of Children and Teenagers 6–18 Years Old - Pelagia Tsakona; Ioannis Kitsatis; Thomas Apostolou; Ourania Papadopoulou; Alexandra Hristara-Papadopoulou (Children)
Background: Few studies are reported on interventions that have been carried out in children and adolescents using diaphragmatic breathing (DB) together with methods like counseling, muscle relaxation, therapeutic exercise, and music therapy. Objective: The goal of the review is to evaluate the effectiveness of DB as complementary therapy in the stress of the pediatric population (6–18 years old). Methods: Detailed research was carried out in the current literature to find relevant studies published from 2010 to October 2024 in PubMed and Cochrane Library. Thirteen studies that fulfilled the inclusion criteria were included in the study. Nine studies involved obese and overweight pediatric populations and the other four involved pediatric patients. Results: The interventions comprised two 8-week studies in an obese pediatric population, seven studies in healthy children and adolescents with normal weight. The studies were based on DB, muscle relaxation, nutrition, counseling, music therapy, and slow breathing exercises. The participants in the intervention group improved in comparison to those in the control group in terms of stress and depression in most included studies, in terms of school performance in two studies, in terms of better family relationships in one study, and showed improvement in anthropometric indicators in two studies. In four studies that involved pediatric patients, stress and fear of medical procedures were reduced. Conclusions: DB can effectively contribute on its own or in combination with other therapeutic methods to improving physiological and psychological indicators in the pediatric population. It is useful to integrate stress management programs that include DB training as clinical practice in primary healthcare and in school schedules for elementary and high-school students.